“RELATIONS BETWEEN AMIR TEMUR AND SULTAN BAYAZID IN THE INTERPRETATION OF A FRENCH ENLIGHTENER” - Israilov Nodir Raximjonovich (Western European Studies, 2025)
The article examines the relationship between Amir Temur and Sultan Bayazid as described by the French Enlightenment thinker of the 18th century, Marie Arouet Voltaire, in his work “Essay on the Manners and Spirit of Nations, and on the Principal Facts of History from Charlemagne to Louis XIII”. Based on the sources of the Timurid era, the study analyzes the French philosopher’s reflections on the contradictions and clashes of interest that arose in the late 14th and early 15th centuries between the rulers of Turan and the Ottoman Empire, the dynamics of the development of diplomatic relations, and the details of the Battle of Ankara. The research employs the comparative and problem-chronological methods. In addition, Voltaire’s views on the negative perceptions that had developed in Western Europe regarding the relations between Amir Temur and Sultan Bayazid are examined on the basis of historical sources. The author analyzes the errors and inaccuracies found in these interpretations and provides critical observations on the matter
Keywords: Amir Temur; Sultan Bayazid; Tahurtang; Transoxiana